a)
a)x=
[tex]3 \sqrt{5} - \sqrt{20} - 4 \sqrt{3} + \sqrt{12} = 3 \sqrt{ 5} -2 \sqrt{5} - 4\sqrt{3} + 2\sqrt{ 3} = ( 3 \sqrt{ 5} -2 \sqrt{5} ) + (- 4\sqrt{3} + 2\sqrt{ 3} ) = \sqrt{5} -2 \sqrt{3}
[/tex]
y=
[tex]7 \sqrt{3} - 4 \sqrt{3} - 2 \sqrt{5} + 3 \sqrt{5} = (7 \sqrt{3} - 4 \sqrt{3}) + ( - 2 \sqrt{5} + 3 \sqrt{5} ) = 3 \sqrt{3} + \sqrt{5} [/tex]
z=
[tex]5 \sqrt{5} - 3 \sqrt{3} + 5 \sqrt{3} - 2 \sqrt{5} = (5 \sqrt{5} - 2 \sqrt{5}) + ( - 3 \sqrt{3} + 5 \sqrt{3} ) = 3 \sqrt{5} + 2 \sqrt{3} [/tex]
x+y+z=
site pt probleme de genul : cymath